FAKTOR-FAKTOR YANG MEMPENGARUHI CAKUPAN KUNJUNGAN BALITA KE POSYANDU DI DESA KEMBANG DAMAI WILAYAH KERJA PUSKESMAS PAGARAN TAPAH KABUPATEN ROKAN HULU - Herawati, Rika (Jurnal Martenity and Neonatal, 2019)
The number of toddlers visiting Posyandu (D / S) only reached 78%, from the target set (85%). Of the 16 existing Puskesmas in Rokan Hulu District, Pagaran Tapah Health Center ranks lowest in achievement (D / S) which is 53.8%. The purpose of this study was to determine the factors that influence the coverage of toddler visits to Posyandu in Kembang Damai Village, the Working Area of Tapah Pagah Tapah Rokan Hulu District. This type of research design is quantitative with a cross sectional study design. The population in this study were all mothers who had toddlers aged> 1 year - 5 years in the Work Area of Pagaran Tapah Health Center, Rokan Hulu Regency, with a total sample of 140 people. The results showed that there was a significant relationship between knowledge and toddler visit coverage to Posyandu (p value = 0.0001, OR value = 4.825), between education and toddler visit coverage to Posyandu (p value = 0.0001, OR value = 4.976) , between jobs with toddler visit coverage to Posyandu (pvalue = 0,0001, OR value = 4,444), between cadre roles and toddler visit coverage to Posyandu (p value = 0,0001, OR = 14,377), between the role of officer and visit coverage toddlers to Posyandu (p value = 0.0001, OR value = 8.582). Suggestions to Pagaran Tapah Health Center in order to improve the quality of counseling about the importance of Posyandu, provide reading material related to posyandu, conduct sweeping of toddlers who do not come when there is a Posyandu schedule, and supervise, conduct training and pay attention to the incentives of agrarian health workers and cadres its performance can be improved.